Differential transcriptional and functional properties of regulatory T cells in HIV‐infected individuals on antiretroviral therapy and long‐term non‐progressors. Issue 5 (26th May 2021) - Shahbaz, Shima; Jovel, Juan; Elahi, Shokrollah
Abstract: Objectives: Regulatory T cells (Tregs) are widely recognised as a subset of CD4 + CD25 + FOXP3 + T cells that have a key role in maintaining immune homeostasis. The impact of HIV‐1 infection on immunological properties and effector functions of Tregs has remained the topic of debate and controversy. In the present study, we investigated transcriptional profile and functional properties of Tregs in HIV‐1‐infected individuals either receiving antiretroviral therapy (ART, n = 50) or long‐term non‐progressors (LTNPs, n = 24) compared to healthy controls (HCs, n = 38). Methods: RNA sequencing (RNAseq), flow cytometry‐based immunophenotyping and functional assays were performed to study Tregs in different HIV cohorts. Results: Our RNAseq analysis revealed that Tregs exhibit different transcriptional profiles in HIV‐infected individuals. While Tregs from patients on ART upregulate pathways associated with a more suppressive (activated) phenotype, Tregs in LTNPs exhibit upregulation of pathways associated with impaired suppressive properties. These observations may explain a higher propensity for autoimmune diseases in LTNPs. Also, we found substantial upregulation of HLA‐F mRNA and HLA‐F protein in Tregs from HIV‐infected subjects compared to healthy individuals. These observations highlight a potential role for this non‐classical HLA in Tregs in the context of HIV infection, which should be investigated further in other chronic viral infections and cancer. Conclusion: Our study has provided a novel insight into Tregs at the transcriptional and functional levels in different HIV‐infected groups. Abstract : This study provides a novel insight into regulatory T cells (Tregs) at the transcriptional and functional levels in HIV‐infected individuals on antiretroviral therapy versus long‐term non‐progressors (LTNPs). A lack of immunosuppressive properties of Tregs in LTNPs may explain the higher propensity for autoimmune diseases in these individuals. ​